LITERASI DIGITAL SEBAGAI PEMICU KEMAMPUAN BERPIKIR KRITIS SISWA SD - Anggun Rianda Putri; Devi Purwanti; Laely Rizki Maulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of digital literacy as a driver of critical thinking skills among elementary school students. In the digital era, students are increasingly exposed to vast amounts of information through various digital platforms, making digital literacy a crucial competency. Digital literacy not only includes the ability to access and use digital technology but also involves evaluating information, understanding content, and making informed decisions critically.This research uses a literature review method by examining and synthesizing relevant studies from national and international journals published between 2020 and 2025. The data collection technique is conducted through documentation of scientific articles, books, and reports related to digital literacy and critical thinking in primary education. The analysis is carried out using a qualitative descriptive approach to identify patterns, relationships, and key findings from previous research. The results show that digital literacy has a significant role in enhancing students’ critical thinking skills. Students with good digital literacy are more capable of analyzing information, distinguishing credible sources, and developing logical reasoning. Furthermore, the integration of digital learning tools supports interactive and student-centered learning, which strengthens critical thinking abilities. This study concludes that strengthening digital literacy in elementary education is essential to foster students’ critical thinking skills in facing the challenges of the digital era.